2016
DOI: 10.5114/wiitm.2016.58617
|View full text |Cite
|
Sign up to set email alerts
|

Cost minimization analysis of laparoscopic surgery for colorectal cancer within the enhanced recovery after surgery (ERAS) protocol: a single-centre, case-matched study.

Abstract: IntroductionThe goal of modern medical treatment is to provide high quality medical care in a cost-effective environment.AimTo assess the cost-effectiveness of laparoscopic colorectal surgery combined with the enhanced recovery after surgery protocol (ERP) in Poland.Material and methodsWe designed a single-centre, case-matched study. Economic and clinical data were collected in 3 groups of patients (33 patients in each group): group 1 – patients undergoing laparoscopy with ERP; group 2 – laparoscopy without ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 36 publications
(29 reference statements)
1
37
0
3
Order By: Relevance
“…The readmission rate (<30 days) was similar in ERAS and CS groups, which indicated that the scientific discharge criteria in ERAS programs would not increase the readmission rate. The results of RCT were consistent with the research of ERAS protocol in laparoscopic colorectal surgery by Pędziwiatr et al …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The readmission rate (<30 days) was similar in ERAS and CS groups, which indicated that the scientific discharge criteria in ERAS programs would not increase the readmission rate. The results of RCT were consistent with the research of ERAS protocol in laparoscopic colorectal surgery by Pędziwiatr et al …”
Section: Discussionsupporting
confidence: 90%
“…As the morbidity rate of overall complications decreased in ERAS group after implementing the ERAS programs, which proved that ERAS programs can safely reduce surgical stress and accelerate patient recovery. We can see that compared with CS group, the patients in ERAS group had low peak of WBCs and ALT,also had higher number of ALB in postoperative days, which Pędziwiatr et al [20][21][22][23] The advantages of ERAS concept manifest in more adequate preoperative preparation before surgery. The detailed preoperative education can reduce patient anxiety through communication.…”
Section: Comparison Of Postoperative Clinical Indexesmentioning
confidence: 83%
“…Enhanced recovery after surgery (ERAS) protocols have become increasingly popular over the past decade. These pathways have proven to significantly reduce postoperative length of stay and costs after colorectal surgery . Fast‐track colorectal surgery has been comprehensively discussed, but few reports have examined the fast‐track program for VATS lobectomy …”
Section: Introductionmentioning
confidence: 99%
“…These pathways have proven to significantly reduce postoperative length of stay and costs after colorectal surgery. [1][2][3] Fasttrack colorectal surgery has been comprehensively discussed, [4][5][6] but few reports have examined the fast-track program for VATS lobectomy. 7,8 Thoracic epidural analgesia (TEA) is generally considered the gold standard of analgesia after thoracotomy.…”
Section: Introductionmentioning
confidence: 99%
“…Their acceptance and consistency of results are accompanied by the development of instruments that enable and facilitate an increasing number of procedures [1][2][3] . However, the cost of this technology 12 creates several limitations that hamper the development of experimental models, especially in small animals.…”
Section: ■ Discussionmentioning
confidence: 99%